Identity as a Moderator and Mediator of Communication Effects: Evidence and Implications for Message Design. Issue 7 (2nd October 2016) - Comello, Maria Leonora G.; Farman, Lisa
ABSTRACT: Advertisements, movies, and other forms of media content have potential to change behaviors and antecedent psychological states by appealing to identity. However, the mechanisms that are responsible for persuasive effects of such content have not been adequately specified. A recently proposed model of communication effects (the prism model) advances the study of mechanisms and argues that identity can serve as both a moderator and mediator of communication effects on behavior-relevant outcomes. These intervening roles are made possible by the complex nature of identity (including multiple self-concepts and sensitivity to cues) and messages that cue the importance of and activate particular self-concepts. This article builds on development of the model by presenting empirical support based on re-analysis of an experiment in which participants viewed either a more-stigmatizing or less-stigmatizing portrayal of a recovering drug addict. In line with the model's propositions, exposure to the less-stigmatizing condition led to increases in perspective taking which then led to more acceptance (mediation by identity), while level of perspective taking also changed the effect of condition on acceptance (moderation by identity). These results provide support for the model's proposition of simultaneous intervening roles. The authors discuss implications for strategic communication research and practice.